Culture of Ambiguity Implications for Self and Social Understanding in Adolescence - Bosacki, Sandra Leanne; SpringerLink (Online service) (Rotterdam : SensePublishers, 2012)
Research shows that the ability to "read others" or to make sense of the signs and symbols evident in human communication has an influence on children's self-conceptions and their social interactions in childhood and adolescence. Given that psychological explanations play a key role in teaching and learning, further research is required, particularly on adolescents within the school context. This book investigates which aspects of these discourse experiences foster the growth of understanding of spirit, emotion, and mind in adolescence. Accordingly, from a co-relational approach to the development of understanding mind and education, this book builds on past and current research by investigating the social and emotional antecedents and consequences of psychological understanding in early adolescence. Specifically, this book explores the question: How do adolescents use their ability to understand other minds to navigate their relationships with themselves and their peers within the culture of ambiguity? To address this question, this book critically examines research on adolescents$1 (Bability to understand mind, emotion, and spirit, and how they use this ability to help them navigate their relationships within the school setting. This book might appeal to a variety of educators and researchers, ranging from early childhood educators/researchers to university professors specializing in socioemotional and spiritual/moral worlds of adolescents. Sandra Leanne Bosacki completed her PhD in Education at the Ontario Institute for Studies in Education of the University of Toronto, Canada. Currently an Associate Professor in the Graduate and Undergraduate Department of Education at Brock University, St. Catharines, Ontario, Canada, she teaches graduate courses in Developmental Educational Psychology and Educational Research. Her teaching and research interests include sociocognitive, emotional, moral, and spiritual development within diverse cultural and educational contexts. She is a contributing associate editor of the International Journal of Children$1 (Bs Spirituality and is the author books The Culture of Classroom Silence and the Emotional Lives of Children (2005; 2008, Peter Lang). She has published research papers in the Journal of Educational Psychology, the Journal of Early Adolescence, Social Development, and Gender Roles: A Journal of Research. She currently resides in Hamilton, Ontario, Canada.s
Keywords: Education; Educational psychology; Education; Educational Psychology